Standardization of hypometric measurements of the Costa Rican Paso Horse - Solano Ocampo, Jose David (2025)
This study aimed to establish, for the first time, official hypometric standards for the Costa Rican Paso Horse (CCP in Spanish), a breed that lacks standardized morphometric parameters for an objective evaluation. A total of 126 specimens registered with ASCACOPA (51 males, 75 females, ages ranging from 0.5 months to 10 years, average body condition score 7) were analyzed using convenience sampling. A total of 22 hypometric variables were evaluated using direct measurements and photographic analysis. Statistical analysis included a descriptive phase to establish breed standards: Welch’s ANOVA for growth patterns by sex and age, and Student’s t-tests for temporal comparisons with 2015 data. Females showed more accelerated growth than males in the foal-to-youngster transition. The temporal analysis revealed significant morphological improvements (2015-2024): increases in head length (2.06-2.35 cm), heart girth (13.04-18.46 cm), and length of croup (up to 7.41 cm), particularly in younger groups. This study provides the first standardized hypometric parameters for the CCP, offering objective tools for its evaluation, selection, and genetic improvement. The results demonstrate the breed’s morphological progress, attributable to selective breeding and management improvements.